Alkali‐Metal‐Ion Batteries: Electrochemical Study of Poly(2, 6‐Anthraquinonyl Sulfide) as Cathode for Alkali‐Metal‐Ion Batteries (Adv. Energy Mater. 48/2020). Issue 48 (22nd December 2020) - Hu, Yanyao; Gao, Yang; Fan, Ling; Zhang, Yanning; Wang, Bo; Qin, Zhihui; Zhou, Jiang; Lu, Bingan
Abstract : In article number 2002780, Ling Fan, Zhihui Qin, Bingan Lu and co‐workers design cross‐linked nano‐flakes poly(2, 6‐anthraquinonyl sulfide) microspheres as an organic cathode for alkali‐metal‐ion batteries. Various electrochemical characteristics are observed and density functional theory calculations support these experimental characterizations.